2015
DOI: 10.1111/bjep.12068
|View full text |Cite
|
Sign up to set email alerts
|

Academically buoyant students are less anxious about and perform better in high‐stakes examinations

Abstract: Background. Prior research has shown that test anxiety is negatively related to academic buoyancy, but it is not known whether test anxiety is an antecedent or outcome of academic buoyancy. Furthermore, it is not known whether academic buoyancy is related to examination performance.Aims. To test a model specifying reciprocal relations between test anxiety and academic buoyancy and establish whether academic buoyancy is related to examination performance.Sample. 705 students in their final year of secondary edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 80 publications
(130 reference statements)
8
58
1
2
Order By: Relevance
“…As a consequence, mathematics anxiety (MA) and test anxiety (TA) have often been investigated separately. Their effects have been examined in relation either to academic performance (Hill et al, 2016;Putwain, Daly, Chamberlain, & Sadreddini, 2015;Roick & Ringeisen, 2017) or to other forms of anxiety, such as general anxiety (Carey, Devine, Hill, & Szűcs, 2017). To the best of our knowledge, different forms of anxiety and any factors protecting against it have not been investigated together, as part of the same study.…”
Section: Anxiety Profiles and Protective Factors: A Latent Profile Anmentioning
confidence: 99%
“…As a consequence, mathematics anxiety (MA) and test anxiety (TA) have often been investigated separately. Their effects have been examined in relation either to academic performance (Hill et al, 2016;Putwain, Daly, Chamberlain, & Sadreddini, 2015;Roick & Ringeisen, 2017) or to other forms of anxiety, such as general anxiety (Carey, Devine, Hill, & Szűcs, 2017). To the best of our knowledge, different forms of anxiety and any factors protecting against it have not been investigated together, as part of the same study.…”
Section: Anxiety Profiles and Protective Factors: A Latent Profile Anmentioning
confidence: 99%
“…Current research on TA has thrived in an era of high stakes testing where approximately 25% -40% of students consistently experience TA. Despite the abundance of work that has been conducted, research continues to produce new insights (e.g., Bellinger, DeCaro, & Ralston, 2015;Putwain, Daly, Chamberlain, & Sadreddini, 2015). For example, Barrows, Dunn and Lloyd (2013) recently reported that test anxiety predicted exam scores and numerous studies have drawn additional at-tention to the important role of students' anxiety and other academic emotions (e.g., Pekrun, Goetz, Frenzel, Barchfeld, & Perry, 2011;Zuckerman, & Spielberger, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2014 identified that students who do well on high-stakes tests view them in a positive manner, compared to students who did poorly viewing them in a vitriolic manner. This research perhaps most clearly mirrors that of Putwain et. al.…”
Section: Impact On Studentssupporting
confidence: 86%
“…Some research has indicated that the ability for teachers to combat anxiety might in fact be inherent. Putwain et. al.…”
Section: Programs Added To Combat Anxietymentioning
confidence: 99%